Queering the city: a social and spatial account of the Mother City Queer Project at the Cape Town International Convention Centre in 2003 - Steyn, Daniel (African Studies, 2023)
The Mother City Queer Project (MCQP) is a themed camivalesque costume party held annually, over a single night in December, in Cape Town since 1994. The event began as a celebration of South Africa's constitutional recognition of the right to sexual difference in the form of a location specific small scale "art party", patronised by the friends and peers of organisers architect Andre Vorster and artist Andrew Putter. Since its inception, the MCQP has grown in size and scale to incorporate a more diverse demographic of partygoer from Cape Town residents, nationally and abroad. The development and growth of the MCQP from an underground community event to one of widespread commercial appeal, increased numbers and popular acceptance can be traced through the MCQP's use of five venues over the course of its first ten years.